2022
DOI: 10.20525/ijrbs.v11i9.2213
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job satisfaction and intention to quit a job: mediating factor job burnout

Abstract: The study explores the aspects of job satisfaction related to the employee's intention to quit the job in the presence of job fatigue and can help decision-makers and administrators in the Jordanian private banking sector retain highly qualified employees.  The current research attempted to investigate the relationship between job satisfaction through its dimensions (satisfaction with pay, satisfaction with promotion, satisfaction with co-workers, satisfaction with emergency bonuses, satisfaction with the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The result of the study showed the existence of an inverted correlation between job satisfactio n a n d the intention to leave. The result revealing that satisfied employees lessen the intention to leave condition is adherent to the results of other studies conducted by Ahmad, et al [36], Park and Johnson [3], Peterson, et al [31], Sopiah and Sangadji [39] and Wijesekara [37]. Undoubtedly, it demonstrated that the more employees feel satisfied with their jobs, the more are they unlikely to leave their current jobs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The result of the study showed the existence of an inverted correlation between job satisfactio n a n d the intention to leave. The result revealing that satisfied employees lessen the intention to leave condition is adherent to the results of other studies conducted by Ahmad, et al [36], Park and Johnson [3], Peterson, et al [31], Sopiah and Sangadji [39] and Wijesekara [37]. Undoubtedly, it demonstrated that the more employees feel satisfied with their jobs, the more are they unlikely to leave their current jobs.…”
Section: Discussionsupporting
confidence: 87%
“…A gradual increase in the levels of dissatisfaction impacts significantly the intention to leave which also affects employee turnover Liu, et al [35]. Ahmad, et al [36] estimated that there is a modera te degree of relationship between job satisfaction and intention as well as a strong intention to leave the job among dissatisfied employees [37]. Th e studies on job satisfaction among bank employees acknowledged that job satisfaction is a key variable and revealed the degree of negative correlation between job satisfaction and the intention to leave [38,39].…”
Section: Relationships Between Job Satisfaction and Intention To Leavementioning
confidence: 99%
“…La satisfacción laboral se define como un estado emocional placentero o positivo resultante de la evaluación del trabajo o de las experiencias laboralesy explica la diferencia entre las expectativas, necesidades o valores de un individuo sobre el trabajo y lo que realmente ofrece (Dodanwala et al, 2023) La satisfacción laboral general se compone de la satisfacción con el trabajo, la satisfacción con el apoyo del supervisor y la satisfacción con las oportunidades de promoción (Singh & Das, 2013). Este constructo es de gran importancia en la gestión organizacional y tiene fuertes implicaciones en el aumento del rendimiento de los empleados (Wnuk, 2017) en la reducción de la rotación laboral (Zaharie et al, 2018) y aumenta el compromiso de los trabajadores (Ahmad et al, 2022). La satisfacción laboral puede verse comprometida por una serie de factores individuales y organizativos, entre estos factores se incluyen la inseguridad e inestabilidad laboral (Reisel et al, 2010) y el exceso de responsabilidades (Gerich & Weber, 2020).…”
Section: Satisfacción Laboralunclassified
“…De hecho, la seguridad laboral es una de las variables sobre la que se desarrolla la satisfacción de los empleados con respecto al trabajo realizado y es la forma en que se obtienen resultados positivos (Wu et al, 2021), la falta de seguridad genera efectos negativos tales como la intención de rotación o el comportamiento contraproducente (Nemteanu et al, 2021). Si nos encontramos con una empresa con empleados no satisfechos esto llevara a la compañía a tener fracasos, así como conflictos 235 personales, burocracia, falta de claridad, problemas de comunicación, malas decisiones, y muchos obstáculos que no permitirán que la compañía, ni sus empleados progresen (Ahmad et al, 2022) Se ha demostrado que variables como la percepción de salud, el apoyo directivo, la infraestructura, equipamiento adecuado, así como la sobrecarga de trabajo pueden ser factores que alteren la satisfacción laboral en el personal de salud en México (Radillo et al, 2021).…”
Section: Satisfacción Laboralunclassified
“…This includes burnout and safety concerns regarding the pandemic for some professions like the medical [12] and education fields [13]. Unsurprisingly, Ahmed et al (2022) empirically found that job satisfaction was statistically significantly inversely related to job burnout [14]. Employees feeling burned out were less satisfied with their jobs.…”
Section: Introductionmentioning
confidence: 99%